The dialectic of literary aesthetics between the old and the new: The theory of deviation as a model - Faiz Al-Islam, Jihad (Journal of Arabic Language Sciences and Literature, 2024)
The study aimed to extract aesthetic transformations and develop its theory. Poetry went through many transformations in its themes and arts, and therefore poetry had to transform in its aesthetics as well. Poetry is renewed from time to time, just as the phoenix is renewed if it becomes weak, so that its vitality, aesthetics, and arousal of feelings remain. The researcher addressed Through this study, literary aesthetics is considered the artistic pillar that distinguishes Arabic poetry, and is considered one of its most important features and important characteristics. It is assumed that there are many developments and theories that these literary aesthetics have undergone, and to achieve the goal of the study, the researcher used the descriptive analytical method as it is suitable for this type of studies. Therefore, he The research included an introduction, four sections, and a conclusion for a set of results reached by the study, including: -Theories of literary aesthetics developed over time, and changed according to time, place, and the theorists who were interested in them. -Literary aesthetics is a new, old term, and modern theories in it are still under development and crystallization in Western literature, as well as Arabic literature, and they still need a lot of maturity, expansion, and intellectual and literary theorizing. -The term literary aesthetics has lived a long life, and it is one of the terms that will remain as long as poetry and literature remain, because the survival of poetry is linked to the survival of humans, their feelings, and their humanity. Poetry has no meaning without beauty, just as there is no meaning for a person without feelings. The study recommended discussing modern aesthetic theories of Western origin and employing them in the field of Eastern and Arab literature and poetry.
Keywords: Literary; aesthetic; dialectical; theories; the old; deviation